2023
DOI: 10.31603/ce.9122
|View full text |Cite
|
Sign up to set email alerts
|

Digital marketing training by Lazismu Medan City to increase the MSMEs competitiveness

Abstract: Digital marketing training is an important solution to increase the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the rapidly growing digital era. This community service aims to provide digital marketing training to MSMEs assisted by Lazismu, Medan City. Identification of partner problems is carried out through meetings with Lazismu leaders to understand the challenges MSMEs face after the Covid-19 pandemic. The training was conducted using interactive lecture and discussion methods, cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…In the digital age, digital marketing has become a game-changing instrument for increasing company competitiveness. MSMEs typically outperform their rivals when they employ digital marketing techniques including content marketing, social media marketing, and SEO (Afandi et al, 2023). Knowing which digital marketing strategies work best for local consumers is essential in Indonesia, as the digital landscape is changing quickly (Bakator et al, 2019).…”
Section: Digital Marketing and Competitivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…In the digital age, digital marketing has become a game-changing instrument for increasing company competitiveness. MSMEs typically outperform their rivals when they employ digital marketing techniques including content marketing, social media marketing, and SEO (Afandi et al, 2023). Knowing which digital marketing strategies work best for local consumers is essential in Indonesia, as the digital landscape is changing quickly (Bakator et al, 2019).…”
Section: Digital Marketing and Competitivenessmentioning
confidence: 99%
“…Additionally, it has been discovered that marketing capabilities and digital marketing, which mediate the relationship between marketing capabilities and marketing performance, significantly improve MSMEs' marketing performance (Sudirjo et al, 2023). It has been demonstrated that providing MSMEs with digital marketing training can boost their competitiveness in the digital age and aid in overcoming obstacles posed by the COVID-19 epidemic (Afandi et al, 2023). H2: There is a significant positive relationship between the implementation of digital marketing strategies by Indonesian MSMEs and their competitiveness.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Tahap ini merupakan pencapaian tujuan dari pembinaan dan pelatihan marketing 4.0, yang merupakan evaluasi proses dan hasil dari kegiatan tersebut dengan lembar evaluasi kepada para peserta mengenai pelaksanaan pelatihan meliputi kemampuan peserta baik dalam teori dan praktik. Pentingnya evaluasi dalam kegiatan ini adalah untuk memastikan bahwa tujuan pelatihan tercapai dan memberikan manfaat yang diharapkan bagi peserta serta menjadi dasar untuk memperbaiki dan mengembangkan kegiatan pelatihan di masa depan (Afandi et al, 2023).…”
Section: Tahap Akhirunclassified
“…By mastering information technology and leveraging digital marketing strategies, SMEs can communicate on a global scale and change the way they do business with customers. Digital marketing training provides scalable support for small industries, allowing them to market their products or services to consumers more easily (Afandi et al, 2023;Ellitan, 2023;Sasa et al, 2021). Another study shows that digital marketing training can indeed improve the knowledge and skills of MSME owners in utilizing social media and online platforms for marketing.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation results show participant satisfaction and increased knowledge and skills in digital marketing. Therefore, digital marketing training is a valuable solution for MSME owners to increase understanding and utilization of social media and online platforms for marketing purposes (Afandi et al, 2023;Arum et al, 2023;Pratama et al, 2023;Supriatna et al, 2022;Wibowo et al, 2022). This, in turn, contributes to increased sales and market reach.…”
Section: Introductionmentioning
confidence: 99%